The relationship between maximum isometric strength and ball velocity in the tennis serve - Baiget, E.; Corbi, F.; Fuentes, J. P.; Fernandez-Fernandez, J. (Journal of Human Kinetics, 2016)
The aims of this study were to analyze the relationship between maximum isometric strength levels in different upper and lower limb joints and serve velocity in competitive tennis players as well as to develop a prediction model based on this information. Twelve male competitive tennis players (mean ± SD; age: 17.2 ± 1.0 years; body height: 180.1 ± 6.2 cm; body mass: 71.9 ± 5.6 kg) were tested using maximum isometric strength levels (i.e., wrist, elbow and shoulder flexion and extension; leg and back extension; shoulder external and internal rotation). Serve velocity was measured using a radar gun. Results showed a strong positive relationship between serve velocity and shoulder internal rotation (r = 0.67; p < 0.05). Low to moderate correlations were also found between serve velocity and wrist, elbow and shoulder flexion - extension, leg and back extension and shoulder external rotation (r = 0.36 - 0.53; p = 0.377 - 0.054). Bivariate and multivariate models for predicting serve velocity were developed, with shoulder flexion and internal rotation explaining 55% of the variance in serve velocity (r = 0.74; p < 0.001). The maximum isometric strength level in shoulder internal rotation was strongly related to serve velocity, and a large part of the variability in serve velocity was explained by the maximum isometric strength levels in shoulder internal rotation and shoulder flexion.